1984
DOI: 10.1038/clpt.1984.54
|View full text |Cite
|
Sign up to set email alerts
|

Sparteine oxidation by the human liver: Absence of inhibition by mephenytoin

Abstract: Recent population data suggest independence of the genetic polymorphisms in mephenytoin and sparteine/debrisoquine oxidation. We used human liver preparations to test whether mephenytoin competes with sparteine for binding to the genetically variable cytochrome P-450, which mediates metabolism of both sparteine and debrisoquine. Mephenytoin failed to inhibit in vitro sparteine oxidation. This provides biochemical evidence that the polymorphism of sparteine/debrisoquine metabolism is not related to that of meph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, there are population differences in the gene frequency for slow debrisoquine 4-hydroxylation Woolhouse et al, 1979;Kalow et al, 1980;Mbanefo et al, 1980). This drug hydroxylation is catalyzed by the same genetically variable cytochrome P-450 which catalyzes sparteine oxidation (Boobis et al, 1983;Inaba et al, 1984b) but is different from the cytochrome P-450 responsible for the polymorphism in mephenytoin metabolism (Kupfer et al, 1982;Inaba et al, 1984a;Jurima et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are population differences in the gene frequency for slow debrisoquine 4-hydroxylation Woolhouse et al, 1979;Kalow et al, 1980;Mbanefo et al, 1980). This drug hydroxylation is catalyzed by the same genetically variable cytochrome P-450 which catalyzes sparteine oxidation (Boobis et al, 1983;Inaba et al, 1984b) but is different from the cytochrome P-450 responsible for the polymorphism in mephenytoin metabolism (Kupfer et al, 1982;Inaba et al, 1984a;Jurima et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…An explanatory hypothesis is the possible biotransformation of QAs in the cow. So far, metabolism of individual QAs has been investigated only in rats, pigs, rabbits, and humans. ,, Studies in rats showed that sparteine was oxidized to lupanine, which was found in the urine of orally dosed rats in vivo (suspected microsomal metabolization), while lupanine was found to be presumably transformed to a hydroxyl derivative through a yet unknown pathway. , Until now, there exists no information regarding the possible metabolization of lupanine into 13α-hydroxylupanine in cows. However, conversion could explain its higher values in the morning milk.…”
Section: Resultsmentioning
confidence: 99%
“…At least two similar forms of human cytochrome P-450 seem to be involved in S-mephenytoin 4-hydroxylation and the molecular basis of the polymorphism has been partly elucidated (Guengerich et al, 1988;Meier et al, 1985;Shimada et al, 1986). Polymorphisms in the oxidation of sparteine/debrisoquine and mepheytoin have been found to be independent entities Jurima et al, 1984). In contrast to the relatively large number of drugs the oxidation of which cosegregates with sparteine/debrisoquine only that of 5-phenyl-5-ethylhydantoin (Nirvanol) and mephobarbitone are known to cosegregate with mephenytoin oxidation in vivo (Jacqz et al, 1986;Kupfer & Branch, 1985;Kupfer et al, 1984).…”
Section: Introductionmentioning
confidence: 99%